Legal Research Perspective through Problem Solution Approach - Yusuf Gunawan (GoAcademica Research & Publishing, 2023)
This study aims to find out what is the point of view of legal research with a problem solution approach (dispute resolution) on legal disputes that exist both in court and outside the court in force in Indonesia. This research method uses a qualitative method with a literature study approach where legal materials are obtained from library books, both printed and electronic. The formulation of the problem for this research are: a. how is the settlement of legal disputes that occur in Indonesia?; b. What are the judges' considerations in their decisions regarding the settlement of legal disputes that occurred in Indonesia? The conclusions of this study are 1. Legal research with a dispute resolution approach (problem solution) can be carried out outside the court and in court where both have advantages, disadvantages and procedures that differ from one another; 2. The legal research approach with out-of-court dispute resolution is difficult to obtain legal documents because it is closed (not published) while dispute resolution through the courts can be analyzed in terms of court decisions, judges' legal considerations and legal findings by judges. It is recommended that the results of dispute resolution outside the court can be obtained openly so that decisions and legal considerations can be examined on existing disputes and laws and other regulations so that they are immediately made to strengthen the legal position of the judge's legal findings.